NOTES ON THE BIOLOGY AND FISHERY OF SHRIMP IN THE SEA OF CORTEZ - CARDENAS, F MAURO (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1947)
Cathaemasia reticulata, collected in Streptocervle t torquata from Antiguo Morelos, Tamaulipas, is redescr Cathaemasia Looss (= Pulchrosoma Travassos); C reticulata (= P pulchrosoma Travassos)
REV SOC MEX HIST NAT
Keywords: NOTES, BIOLOGY, FISHERY OF SHRIMP, SEA OF CORTEZ; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL (ZOOLOGIA)